Imino-pyridyl and PPh3 mixed ligand complexes of Cu(I)X (X: I, Br, and Cl): Synthesis, structure, DFT and Hirshfeld surface studies - Mondal, Jahangir; Manna, Amit Kumar; Patra, Goutam Kumar (European Journal of Chemistry, 2020)
Three new halide bridged copper(I)complexes [Cu2(µ-L)(µ-X)2)(PPh3)2]n {X: I (1), Br (2) and Cl (3)} have been synthesized by the reaction of Cu(I)X (X: I, Br and Cl) with PPh3 and the polydentate imino-pyridyl ligand L. Interestingly, copper(I) forms coordination polymers with the ligand L and the co-ligand PPh3. These complexes 1, 2 and 3 have been characterized by elemental analysis, IR, UV-Vis, and NMR spectroscopy. The crystal structure of the complex 2 has been determined by single-crystal X-ray analysis. Crystal data for complex 2: triclinic, space group P-1 (no. 2), a = 9.471(10) Å, b = 11.043(11) Å, c = 13.215(18) Å, α = 65.853(18)°, β = 69.94(2)°, γ = 67.350(14)°, V = 1135(2) Å3, Z = 2, T = 296.15 K, μ(MoKα) = 2.806 mm-1, Dcalc = 1.535 g/cm3, 4059 reflections measured (3.462° ≤ 2Θ ≤ 44.818°), 2639 unique (Rint = 0.0637, Rsigma = 0.1621) which were used in all calculations. The final R1 was 0.0700 (I > 2σ(I)) and wR2 was 0.2207 (all data). Hirshfeld surface analysis of the complex 2 showed H···H, N···H and Br···H interactions of 55.9, 14.4 and 4.1%, respectively. MEP of ligand L reflects the whole molecule is reddish yellow in color because of equally distributed electron density over the molecule. For this reason, the ligand is supramolecularly arranged via -CuI2-µ-X2 rhomboid core in the complex 2. The ligand L is non-emissive at room temperature in dichloromethane, whereas the complexes 1, 2 and 3 are photoluminescent. DFT and Hirshfeld surface studies have also been performed for complex 2.